The Effect of Brand Ambassador Ahn Hyo-Seop’s Endorsement on Consumer Satisfaction with Mi:Seum Products - Andreyani Andreyani; Khaerudin Imawan (International Journal of Social Service and Research, 2026)
In the New Media era, Instagram serves as a strategic interactive marketing platform for the beauty industry. Beauty brands are capitalizing on the global Korean Wave phenomenon extensively through international celebrity endorsements, as seen in MI:seum's collaboration with South Korean actor Ahn Hyo-Seop. Although existing literature primarily examines short-term impacts such as brand awareness, a significant research gap remains regarding long-term post-purchase effects, particularly overall consumer satisfaction. Based on Source Credibility Theory, this study aims to examine the effect of Brand Ambassador Ahn Hyo-Seop's endorsement credibility on consumer satisfaction with MI:seum products among followers of the Instagram account @mi:seum.id. Using a quantitative explanatory approach with a causal research design, this study sampled active followers from a total population of 22,000. Using the Slovin formula with a 10% margin of error, the base sample of 100 was expanded to 120 respondents through Simple Random Sampling to improve statistical accuracy. Data were collected through a validated and reliable structured digital questionnaire, and analyzed using Simple Linear Regression via IBM SPSS 25.0. The partial hypothesis test (t-test) yielded a calculated t-value of 10.103 ($p < 0.001$), which confirmed that endorsement credibility positively and significantly influenced consumer satisfaction. The overall regression model showed a strong fit ($F = 102.080, p < 0.001$), with a coefficient of determination ($R^2$) of 0.464, indicating that 46.4% of the variance in consumer satisfaction was directly influenced by Ahn Hyo-Seop's endorsement credibility. These findings empirically validate the Source Credibility Theory in the digital ecosystem, indicating that positive perceptions of international brand ambassadors effectively drive sustained evaluative responses in consumers.